The Mauritanian [videorecording (DVD)] - Cumberbatch, Benedict, 1976-; Foster, Jodie; Rahim, Tahar, 1981-; Levi, Zachary, 1980-; Usmani, Saamer; Slahi, Mohamedou Ould (Universal Pictures Home Entertainment, 2021)
The true story of Slahi's fight for freedom after being detained and imprisoned without charge by the U.S. Government for years. Alone and afraid, Slahi finds allies in defense attorney Nancy Hollander and her associate Teri Duncan who battle the U.S. government in a fight for justice that tests their commitment to the law and their client at every turn. Their controversial advocacy, along with evidence uncovered by a formidable military prosecutor, Lt. Colonel Stuart Couch, uncovers shocking truths and ultimately proves that the human spirit cannot be locked up.